Greening thy neighbor: How the United States inflation reduction act drives climate finance globally - Daniel Marcel te Kaat; Alexander Raabe; Yuanjie Tian (Asian Development Bank (ADB), 2024)
Industrial policies greening the economy aim to accelerate the transition to net zero. We show that the United States (US) Inflation Reduction Act improved the supply of climate finance globally. Using granular data on global investment funds, we identify a novel international spillover channel of industrial policies. Sustainable global investment funds received more inflows upon the act announcement, in turn increasing their cross-border portfolio investments worldwide. Recipient economies better prepared to address climate change benefited most from sustainable global funds' additional investments. Non-US domiciled sustainable funds investing outside of the US account for most of the spillovers. The results are robust to a rich set of controls and fixed effects, absorbing recipient economies' demand for foreign funds. Thus, global investment funds have become an important conduit for the international spillover of climate policies.
Keywords: F3; G1; G2; Q5; 330; sustainable finance; climate policy; industrial policy; cross-border spillover; portfolio reallocation; portfolio capital flows; investment fund; Inflation Reduction Act